2008
DOI: 10.1158/1055-9965.epi-07-2510
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Bioavailability of Sulindac in Capsule and Tablet Formulations

Abstract: The cyclooxygenase (COX)-2 enzyme appears to be an important target for cancer chemoprevention. Given the recent emergence of potentially serious cardiovascular toxicity associated with selective COX-2 inhibitors, nonsteroidal antiinflammatory drugs (NSAIDs), which inhibit both COX-1 and COX-2, have received renewed attention as candidate chemoprevention agents. Sulindac has shown consistent chemopreventive potential in preclinical studies as well as in a limited number of clinical trials reported to date. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Samples were analyzed by HPLC (Reid et al, 2008). The HPLC system (Shimadzu, Kyoto, Japan) consisted of a pump (CBM-20A) with a UV detector (SPD-20A) and an autosampler (SIL-20A).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analyzed by HPLC (Reid et al, 2008). The HPLC system (Shimadzu, Kyoto, Japan) consisted of a pump (CBM-20A) with a UV detector (SPD-20A) and an autosampler (SIL-20A).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the higher bioavailability of sulindac sulfi de after metabolic reduction of sulindac, makes this metabolite an ideal inhibitor of LF, since sulindac sulfi de will be more readily available in circulation than sulindac sulfone. [ 28 ] LF protease activity inhibition studies also revealed that both sulindac sulfi de and sulindac sulfone were good inhibitors of LF protease activity. For sulindac sulfi de, an IC 50 of 19.1 μ M was observed (Supplemental Figure 4c), suggesting that this metabolite could be better inhibitor of the anthrax toxin that its parent drug sulindac (IC 50 = 173 μ M).…”
Section: Sulindac Metabolic Derivatives As Inhibitors Of Lf Toxinmentioning
confidence: 92%
“…After a typical dosage of 150 mg, the maximum concentration of sulindac in human blood plasma is of 5.71 ± 2.17 μ g/mL, with a mean half life of 7.8 h. [ 28 ] Sulindac is actually a prodrug that upon oral administration is transformed by the liver to the reduced sulfi de and the oxidized sulfone. Sulindac sulfi de is the actual COX(I/II) inhibitor, while the sulindac sulfone has not been found to have an anti-infl ammatory activity.…”
Section: Sulindac Metabolic Derivatives As Inhibitors Of Lf Toxinmentioning
confidence: 99%
“…Ongoing concerns regarding the cardiovascular toxicity of selective COX-2 inhibitors [24, 25] have prompted renewed interest in non-selective COX inhibitors, such as sulindac, for chemopreventive applications. [26] In this context, we conducted a randomized, double-blind, phase II trial of sulindac versus placebo among current or former smokers with histologically-confirmed bronchial dysplasia at baseline.…”
Section: Introductionmentioning
confidence: 99%